Thermal and mass diffusion in chemically reactive, radiative hybrid nanofluid (Cu and TiO2) flow over a rotating disk - Raja Ram Meena; Pooja Sharma (International Journal of Thermofluids)
The current research work is focused on thermal and mass transfer analysis on a hybrid nanofluid (water as a base fluid,) flow over a rotating disk with free convective, viscous dissipation, MHD, and radiation effects. The model was prepared in terms of the nonlinear PDEs and transformed into ODEs by using similarity analysis. Subsequently, it's solved numerically and graphically by ‘using the ‘bvp4c’ tool in MATLAB. The results depict that the fluid radial velocity can be enhanced by reducing the volume fraction of TiO2, and the azimuthal velocity of the disc is improved, due to nanoparticle TiO2 vol fraction and buoyancy force. Mass diffusion becomes low in the case of highly chemically reactive conditions. The flow characteristics are significantly influenced by variations in heat generation, thermal radiation, and MHD parameters. The calculated values of shear stress, Nusselt, and Sherwood numbers at the surface of the disk are also incorporated for complete verification. The deliberated model and graphical results have significant contributions in many fields like rotating machinery, lubricants, computer storage devices, viscometry, crystal growth process, etc.